P.068 Real world experience with Fingolimod in Canada. (2nd June 2017) - Bhan, V; Lapierre, Y; Devonshire, V; Emond, F; Morrow, SA; Burton, JM; Oh, J; Haddad, P; Schecter, R
Abstract : Background: The Gilenya ® Go Program TM offers education and support services, including coordination of first dose observation (FDO) and follow-up contact to reinforce monitoring recommendations and compliance in fingolimod-treated relapsing-remitting multiple sclerosis (RRMS) patients.Methods: Data were analyzed for patients enrolled in the Canadian Gilenya ® Go Program TM from March 2011 to January 2016. The retention to fingolimod therapy, reasons for treatment discontinuation and incidence of adverse events (AEs) during treatment are reported.Results: At data cut-off, 3956 patients had completed FDO; 3201 patients were being actively treated. Mean age at enrolment was 41.0 years; 74.9% patients were female. The overall fingolimod exposure was 7869 patient-years. Most recent previous therapies (n=3746) included interferons (43.3%) and glatiramer acetate (29.6%). Most common reasons for switching to fingolimod (n=3674) was lack of efficacy (31.8%). Retention to therapy at data cut-off was 81.3%. AEs (45.2%) were the most common reason (n=334) for treatment discontinuation and included low lymphocyte count/abnormal hematology values (13.8%), gastrointestinal disturbances (6.9%), and elevated liver enzyme levels (7.8%). Adherence to recommended ophthalmic examination was 92.4%.Conclusions: In real-world clinical practice in Canada, adherence to both fingolimod treatment and monitoring was high. The Gilenya ® Go Program™ helps to meet the safety monitoring recommendations for fingolimod-treated RRMS patients.